Unveiling Healthcare Professionals' Insights via Knowledge, Attitude and Practice on Materiovigilance: A Multi-Centric Prospective Interventional Study - Mahabasha, Sameer; Wali, Shashikala; Reddy, Mandati Santhosh (International Journal of Pharmaceutical Investigation, 2026)
Background Materiovigilance is essential for ensuring safety and efficacy of medical devices by monitoring and reporting adverse events. Despite its importance, healthcare professionals’ Knowledge, Attitude, and Practice (KAP) regarding materiovigilance remain underexplored in India. This study evaluates the impact of an educational intervention on the KAP of healthcare professionals in a multi-centric setting. Materials and Methods A prospective, interventional study was conducted among physicians, nurses, and pharmacists in a privately-owned tertiary healthcare facility, a public tertiary care hospital and two primary healthcare centres. A validated questionnaire assessed baseline KAP, followed by an awareness-cum-sensitization program comprising and informational leaflets. Post-intervention assessments were conducted to evaluate improvements. Data were analyzed using SPSS, with a p-value below 0.05 indicating statistical significance. Results A total of 256 healthcare professionals participated in the study. Pre-intervention, knowledge was inadequate, with only 49.6% of physicians, 39.0% of nurses, and 46.7% of pharmacists scoring above the adequacy threshold. Attitude toward materiovigilance was positive, yet practice remained suboptimal, with low adverse event reporting. Post-intervention, knowledge scores significantly improved across all groups (p<0.05), with 89.9% of physicians, 80.5% of nurses, and 66.7% of pharmacists demonstrating adequate knowledge. Attitude scores also increased, though practice improvements were moderate. Conclusion Educational interventions enhance knowledge and attitude toward materiovigilance, yet practice remains a challenge. Strengthening institutional support, simplifying reporting procedures, and encouraging a supportive reporting culture can increase engagement and compliance, ultimately ensuring better patient safety.
Keywords: Materiovigilance; Adverse Event Reporting; Healthcare Professionals; KAP Study; Medical Device Safety; Intervention.